##### Ad

related to: K

If

**k**= 1, then this series diverges by the nth term test, because lim(n→∞) n! = ∞. ---------- Assuming**k**> 1, now we use the Ratio Test: r = lim(n→∞) [((n+1)!)^2 / (**k**...1 Answers · Science & Mathematics · 07/04/2013

y = 2x +

**k**← this is a line y = x² +**k**x + 5 ← this is a curve y = y → 2 points → 2 solutions for x x² +**k**x + 5 = 2x +**k**x² +**k**x + 5 - 2x -**k**= 0 x² + x.(**k**- 2) + (5 -**k**) = 0 Polynomial...3 Answers · Science & Mathematics · 22/01/2016

f(x) =

**k**- x² ← this is the curve y = 4x - 9 ← this is the line ... us only one point, so only one solution to the equation 4x - 9 =**k**- x² x² + 4x - 9 -**k**= 0 x² + 4x - (9 +**k**) = 0 ...4 Answers · Science & Mathematics · 24/09/2015

a[

**k**] = 1/ln(**k**)^ln(**k**) a[**k**+1] = 1/ln(**k**(1+1/**k**))^ln(**k**+1) = 1/( ln(**k**) + ln(1+1/**k**))^ln(**k**+1) = 1/ ( ln(**k**)^ln(**k**+1) ( 1+ (ln(1+1/**k**)/ln(**k**) )^ln(**k**+1) a[**k**]/a[**k**+1] =ln(**k**)(1+(ln...3 Answers · Science & Mathematics · 18/04/2007

"Solve for

**k**in terms of**k**" doesn't make sense:**k**=**k**is obvious. I...thing and see if we can get a cleaner statement of the relationship between x and**k**: log(base2)x+log(base2)(x+5)=**k**log(base2) [x(x+5)] =**k**{by properties of...2 Answers · Science & Mathematics · 19/10/2009

========= x^2 +

**k**+ 6 = kx +3x x^2 -x(**k**+3) + (**k**+6) = 0 The equation will have equal ... happens when the discriminant is zero. So, solve (**k**+3)^2 - 4(**k**+6) = 0**k**^2 + 6k + 9 - 4k - 24 = 0**k**^2 + 2k - 15 = 0 (**k**+5)(**k**-3...2 Answers · Science & Mathematics · 14/10/2012

This only true if

**K**is also a metric space. Otherwise there are counterexamples.... Now to prove the claim: Forward direction: Suppose**K**is compact and A = (x_n) is a sequence in**K**. We...2 Answers · Science & Mathematics · 16/10/2010

**k**=ideal gas constant**k**=universal gas constant**k**=constant proportional**k**=0.08205 L.atm/mol.**K**(if you're gonna use liter) or**k**=82.05ml.atm/mol.**K**(if you're gonna use ml)**k**is also be R it ...1 Answers · Science & Mathematics · 28/04/2008

... 6/(

**k**+1) - 1/(**k**) = 1 ← note:**k**≠ 0 or -1 or 6(**k**) - (**k**+1) = (**k**+1)(**k**) or 6**k**-**k**- 1 =**k**² +**k**or 0 =**k**² +**k**- 6**k**+**k**...4*3 ) ] / 2**k**= [ 4 ± 2√3 ) ] / 2**k**= 2 ± √3**k**= { 2 - √3, 2 + √3 }**k**~ { 0.2679, 3.7321 }3 Answers · Science & Mathematics · 11/09/2010

**k**= (**k**+15)/3*(**k**-1) ==> multiply both sides by 3(**k**-1) to get rid of fractions 3k(**k**-1) =**k**+15 ==> expand the LHS 3k^2-3k =**k**+15 ==> move everything to the LHS 3k^2-4k-15=0 actually this does...3 Answers · Science & Mathematics · 21/07/2007

##### Ads

related to: K